Penerapan Teknologi Akuaponik Teknik Media Bed: Dasar Penentuan Rasio Kepadatan Ikan yang Ideal - Joni Johanda Putra; Taufik Budhi Pramono; Agung Cahyo Setyawan (Politeknik Kelautan dan Perikanan Sorong, Indonesia, 2021)
This study aims to determine the effect of differences in fish density and media volume on the growth and survival of tilapia (Oreochromis niloticus) and to determine the effective density in aquaponic culture using bed media techniques. In this study, parameters were measured including the specific growth rate of fish, feed conversion ratio, water quality and survival rate. The experimental design used in this study was a completely randomized design (CRD) with 4 treatments (1 fish stocking ratio/L media bed; 2 fish/L media bed; 3 fish/L media bed; and 4 fish/L media bed). ) and was repeated three times in this study. The results showed that the average length of the final fish was between 6.5 – 9.5 cm, and the average weight of the final fish was in the range of 5 – 17 grams. The optimum density value and the best fish productivity from this study were at P4 with a stocking density of 20 fish per liter of water with significant results.